Steady and pulsating flow past a heated rectangular cylinder(s) in a channel - Saxena, Ashish (2019)
In the present study, the effect of laminar steady (Re=100, Pr=0.74) and pulsating flow (4 Hz and amplitude 0.4) is numerically studied over a centrally located heated rectangular cylinder of varying aspect ratio (W/H=1 to 8) in a confined channel using finite volume method. To study the influence of channel walls at a fix distance, eccentric placement of the highest aspect ratio cylinder(s) with two gap ratios (B/H) of 5 and 0.5 is done. Isotherms and streamlines of the flow are presented along with lift and drag coefficients. Further, fast Fourier transform (FFT) spectral analysis is performed to evaluate the vortex shedding frequency of the flow upon interaction with the cylinder(s). For single cylinder at the center position in the channel, natural vortex shedding and “lock-on” shedding occurs for lower-aspect-ratio cylinder under steady and pulsating flow, respectively. An increase in aspect ratio has a suppressing effect on the vortex shedding with a substantial decrease in the heat transfer over the cylinder. Placing two cylinders (W/H=8) at a geometrically symmetrical eccentric location of B/H=5 shows an extra peak at half of the flow inlet frequency in FFT spectral curve that possibly confirms the lock-on shedding with increased heat transfer over the cylinder.